1968
DOI: 10.2172/4501526
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body NMR Spectrometer.

Abstract: This report was prepared as an account of Government sponsored work. Neither the United States, nor the Commi!lsion, nor any person acting on behalf of the Commission: A. Makes any warranty or representation, expressed or implied, with respect to the accuracy, completeness, or usefulness of the Information contained in this • report, or that the use of any Information, apparatus, method, or process disclosed in this report may not Infringe privately owned rights; or B. Assumes any liabilities with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Already in 1965, proton NMR relaxation times of living frog muscle were published [13], and in 1968 the first whole-body spectrum of a rat was taken [14]. In the 1960s and 1970s a very large amount of work was published on relaxation, diffusion, and chemical exchange of water in cells and tissues of all sorts.…”
Section: Resistive Electromagnets the Beginning Of Analytical Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Already in 1965, proton NMR relaxation times of living frog muscle were published [13], and in 1968 the first whole-body spectrum of a rat was taken [14]. In the 1960s and 1970s a very large amount of work was published on relaxation, diffusion, and chemical exchange of water in cells and tissues of all sorts.…”
Section: Resistive Electromagnets the Beginning Of Analytical Nmrmentioning
confidence: 99%
“…After early attempts on whole animals [14], numerous studies of live, intact animals took place in the 1970s to investigate anatomy, biochemistry, and physiology in vivo [38][39][40][41], also using perfused organs (e.g., [42][43][44]). In 1979, Britton Chance at University of Pennsylvania (PA, USA), contacted OI (UK) to design and build the first horizontal 1.5 T/20 cm magnet for metabolic research.…”
Section: Biomedical and Preclinical Mri And Mrs Researchmentioning
confidence: 99%
“…Since as early as 1959, when Singer utilized NMR to assess blood flow rates in the tail of a mouse (17), the mouse has played an important role in the development of many pioneering accomplishments in both MRI and MRS (18)(19)(20)(21)(22)(23)(24). With the advent of genetic engineering, this small animal has itself become the center of interest, and dedicated MR technologies have been adapted to help study and better understand the proliferation of mouse models of human diseases.…”
Section: Mr Of Transgenic Micementioning
confidence: 99%
“…The sensitivity of the nucleus to its electronic environment in a molecule (the "chemical shift") and spinspin interactions were seen at first in the nuclear physics community as annoying features, but the potential of NMR spectroscopy for analytical studies was soon revealed by the discovery of the 3 peaks of ethanol in Purcell's group [8]. Almost none of the early applications of NMR were medical, although a large amount of work was published on relaxation, diffusion, and exchange of water in cells and tissues, even in living human subjects [10] and whole animals [11].…”
Section: Historical Introductionmentioning
confidence: 99%